2016
DOI: 10.3791/54092
|View full text |Cite
|
Sign up to set email alerts
|

Method to Produce Durable Pellets at Lower Energy Consumption Using High Moisture Corn Stover and a Corn Starch Binder in a Flat Die Pellet Mill

Abstract: A major challenge in the production of pellets is the high cost associated with drying biomass from 30 to 10% (w.b.) moisture content. At Idaho National Laboratory, a high-moisture pelleting process was developed to reduce the drying cost. In this process the biomass pellets are produced at higher feedstock moisture contents than conventional methods, and the high moisture pellets produced are further dried in energy efficient dryers. This process helps to reduce the feedstock moisture content by about 5-10% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…formation. Mechanical pretreatment of starch samples led to defect accumulation in the crystal structure, thus causing the disruption of double helices of amylopectin and single helices of amylase due to the rupture of hydrogen or glycosidic bonds, as well as the release of interspersed amylose molecules into the amorphous phase ( Figure 6) [10,26,[35][36][37]. It was shown that longer duration of mechanical activation leads to gradual amorphization of the crystalline structure of A-, B-, and C-type starches, so their crystallinity degree decreases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…formation. Mechanical pretreatment of starch samples led to defect accumulation in the crystal structure, thus causing the disruption of double helices of amylopectin and single helices of amylase due to the rupture of hydrogen or glycosidic bonds, as well as the release of interspersed amylose molecules into the amorphous phase ( Figure 6) [10,26,[35][36][37]. It was shown that longer duration of mechanical activation leads to gradual amorphization of the crystalline structure of A-, B-, and C-type starches, so their crystallinity degree decreases.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, mechanical pretreatment of cellulose in a planetary ball mill gives rise to a reactive product that is characterized by disordered ultrastructure, increased specific surface area, and reduced crystallinity degree [23,24]. For starch, mechanical pretreatment also reduces the grain size and increases the content of the amorphous phase, making it possible to alter the hydrating and paste-forming properties of modified starch [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Idaho National Laboratory (INL) has developed a high-moisture pelleting process that can help to reduce pellet-production costs significantly. Tumuluru [21][22][23], Tumuluru et al [40], Bonner et al [41], and Hoover et al [42] have all successfully tested this process on both woody and herbaceous biomass, as well as chemically pretreated biomass, in both pilot and commercial-scale pelleting systems. In this process, the biomass is pelleted at a higher moisture content of > 15% (w.b.…”
Section: High-moisture Pelleting Processmentioning
confidence: 99%
“…Upon cooling, solid bridges are formed between components that strengthen the pellet [14]. By the combined interaction between the moisture content and the biomass components (proteins, starch and/ or lignin) at high temperature and pressure, the proteins present in the biomass undergo plasticization/denaturation and the starch added as binders undergoes gelatinization that promotes better binding of the particles [14,15]. Also, the waxes and lignins present in the biomass could have undergone a glass transition at 40-50 °C and 65-75 °C, respectively, as reported by Stelte et al [11].…”
Section: Binders and Pellet Stabilitymentioning
confidence: 99%